Teacher’s Assistant - Priyadharshini.S, Tharani.S (International Journal of Modern Agriculture, 2021)
User’s The project entitled â€œTeachers Assistantâ€ has been developed under Android as front end and SQLite 3.23.3 as back end.The main aim of this project is to help the staff members to store their dataâ€™s easily.Various reports are possible such as notes,Schedule data,Attendences data and student data. Each member has unique username and password. Admin can add the member details in the app. Various reports are possible such as notes,Schedule data,Attendences data and student data.The main aim of this project is to help the staff members to store their dataâ€™s easily.Members login to this app and then upload their notes that can help the students to note their details.